EFEKTIVITAS KINERJA PEGAWAI KANTOR CAMAT SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Putra, Tri Arga; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Sentajo Raya District Office is a government agency or public organizations in the implementation refers to standardization in the service of showing the duties and functions of each part that is in Head Office Sentajo Raya. As a government agency that includes the human resources that employees who work at thee instution. Camat Sentajo Raya Kabupaten Kuantan Singingi implement development programs work performance of employees. However, if viewed directly in the field then there’s also a mismatch with their responsibilities. The work should be completed in a short time could be delayed, employees profesionalism in providing services to the community is still poor and own problems that occurred. This study used qualitative research methods to study descriptive data. The concept of using the concept of performance theory. Theory Hasibuan (2002:22). In collecting the data, the researcher used interview, observation, and documentation. By using key informants as a source of information and triangulasi techniques for analysis data. These results indicate that the district office performance Sentajo Raya still not working optimally. Still, there are employees who work not in accordance with its function and follow the vision and mission of the district Sentajo Raya. Required training for office workers to enhance the performance and capabilities Sentajo Raya district office employees to comply with the district of mission vison Sentajo Raya. Keyword : Performance, Vision Mission, Efectivity